Association between Carotid Wall Shear Rate and Arterial Stiffness in Patients with Hypertension and Atherosclerosis of Peripheral Arteries - Vadim V. Genkel; Alexey O. Salashenko; Tatyana N. Shamaeva; Veronika A. Sumerkina; Igor I. Shaposhnik (International Journal of Vascular Medicine)
Aim. To evaluate carotid wall shear rate (WSR) in association with local and regional vascular stiffness in patients with hypertension (HTN) and atherosclerosis of peripheral arteries and to study the pattern of change of WSR in patients with HTN with increasing severity of peripheral artery atherosclerosis. Materials and Methods. Study involved 133 patients with HTN, 65 men and 48 women, aged in average 57.9±10.8 years. All patients were divided into four groups in accordance with ultrasound morphologic classification of vessel wall. Duplex scanning of carotid and lower limb arteries was performed. Carotid-femoral (cfPWV) and carotid-radial (crPWV) pulse wave velocity (PWV) were measured. Local carotid stiffness was evaluated by carotid ultrasound. Results. WSR of patients with plaques without and with hemodynamic disturbance was 416±128 s−1 and 405±117 s−1, respectively, which was significantly less than the WSR in patients with intact peripheral arteries – 546±112 s−1. Decreased carotid WSR was associated with increased crPVW, cfPWV, Peterson’s elastic modulus, decreased distensibility, and distensibility coefficient. Conclusion. In patients with HTN and atherosclerotic lesions of peripheral arteries, it is registered that the carotid WSR decreased with increasing severity of atherosclerosis. Decreased carotid WSR is associated with increased local carotid stiffness, regional vascular stiffness of muscular, and elastic vessels.